Global cultural governance. Decision-making concerning world heritage between politics and science - Schmitt, Thomas M. (ERDKUNDE, 2009)
The issue of heritage has become fashionable in the cultural sciences, with UNESCO’s World Heritage programme attracting a great deal of academic attention. However, there has been no social study of the global level of World Heritage governance, which can be seen as an example of global cultural governance – societal governance and regulation of cultural expressions and cultural orientation systems. This paper first discusses the concept of cultural governance as an approach for social and cultural sciences and applies it to the specific case of World Heritage. Empirically, the paper is based essentially on an observation of two sessions of the UNESCO World Heritage Committee in 2006 and 2007. It is shown that within the Committee, and to a certain extent also within UNESCO’s official advisory bodies, there are different understandings of key concepts (such as outstanding universal value) and key instruments (such as World Heritage List in Danger, benchmarks); however, this pluralism need not necessarily be detrimental to the successful governance of World Heritage properties. The practice of decision-making on the basis of “far-fetched facts” is a problem for the credibility of the global institutions in multilevel governance systems or international regimes.